2021
DOI: 10.3389/fpsyg.2021.528862
|View full text |Cite
|
Sign up to set email alerts
|

Persistence Conditions of Institutional Entities: Investigating Copredication Through a Forced-Choice Experiment

Abstract: The conditions under which certain complex polysemous nominals can sustain coherent sense relations (informally, can “survive”) is investigated through a two-alternative forced choice experiment. Written scenarios were constructed which permitted copredication, through which multiple, semantically different sense types are associated with a single nominal. Participants were presented with two scenarios involving a polysemous nominal (e.g., bank, city) and had to select which scenario (and, hence, which combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…(e.g., there is no Dominant-Subordinate sense ordering preference). There is empirical evidence that persistence conditions of institutional entities in copredication are not significantly determined by sense frequency, but rather sense complexity (Murphy, 2021c). These findings are problematic for Löhr and Michel's model, since sense predictability most directly stems from a nominal's sense frequency profile.…”
Section: Conceptual Issuesmentioning
confidence: 91%
See 2 more Smart Citations
“…(e.g., there is no Dominant-Subordinate sense ordering preference). There is empirical evidence that persistence conditions of institutional entities in copredication are not significantly determined by sense frequency, but rather sense complexity (Murphy, 2021c). These findings are problematic for Löhr and Michel's model, since sense predictability most directly stems from a nominal's sense frequency profile.…”
Section: Conceptual Issuesmentioning
confidence: 91%
“…The sense frequency profiles reported in Murphy (2021a) reveal that the expectations/frequencies for BOOK and CITY are not equally balanced between senses, and that frequency has no statistically significant relationship with predicate order acceptability (e.g., there is no Dominant–Subordinate sense ordering preference). There is empirical evidence that persistence conditions of institutional entities in copredication are not significantly determined by sense frequency, but rather sense complexity (Murphy, 2021c). These findings are problematic for Löhr and Michel's model, since sense predictability most directly stems from a nominal's sense frequency profile.…”
Section: Methodological Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Going beyond this, in Murphy (2021c) it was shown that what I called the "persistence conditions" for copredication (the conditions under which certain complex polysemous nominals can sustain coherent sense relations in a brief narrative which "takes away" certain senses until the object referred to is reduced in sense number) are also correlated significantly with semantic complexity, not sense frequency. This provides further evidence for the centrality not of prediction, but of semantics (see Murphy 2023bMurphy , 2024a.…”
Section: Much Ado About Nothing: the Absence Of Frequency Effects In ...mentioning
confidence: 99%
“…Here, they inaccurately characterize the "experiments by Murphy", which concern basic structures like "The X was P and Q", or "The P and Q X", but also longer sentences with more complex predicates and prepositional phrases. For even more rich contexts, see Murphy (2021c) and the narratives tested in this experimental report. The important point to stress here is that even though M&L characterize ordering effects as obtaining at the sentence level, with "rich context", even basic phrases exhibit the ISC bias.…”
Section: Anyone But You: Attempts To Diverge From Murphy (2021a)mentioning
confidence: 99%